Clinical Features and Treatment of Fibrous Histiocytomas of the Tongue: A Systematic Review - Nguyen,Austin (2018)
Abstract Introduction Benign fibrous histiocytomas are common lesions of the skin that rarely affect the tongue. Such cases are available in the literature exclusively as case reports. Similarly, malignant fibrous histiocytoma, now classified as undifferentiated pleomorphic sarcoma, is exceedingly rare in the tongue and not fully understood. Objectives This study systematically reviews the available literature discussing the clinical and pathological features of malignant and benign fibrous histiocytomas. Data Synthesis A total of 20 cases were included in this review. Patient-level data were extracted from cases to include clinical presentation, workup, treatment, and outcome. Conclusion Benign fibrous histiocytomas are consistent in clinical and histopathologic presentation. Surgical treatment provides excellent outcome, with no recurrence in all excised cases. Malignant tumors have a more aggressive clinical and pathological presentation. Surgical treatment with possible adjuvant radiotherapy resulted in recurrence in 40% of cases (follow-up of 24 months), and death due to disease in 47% of patients (follow-up of 19 months).